Fabrication and photoelectric properties of Er3+ and Yb3+ co-doped ZnO films. (30th November 2015) - Feng, Wei; Wang, Xiangfu; Meng, Lan; Yan, Xiaohong
Abstract: In this paper, the Er 3+ and Yb 3+ co-doped ZnO films deposited by a novel thermal decomposition method under different annealing temperature process have been reported. The effects of annealing temperature on the morphology and properties of the films are systematically studied. The resulting spectra demonstrate that the Er 3+ and Yb 3+ co-doped ZnO films possessed the property of up-conversion, converting IR light into visible light that can be absorbed by amorphous silicon solar cell. After all, inner photoelectric effect of the Er 3+ and Yb 3+ co-doped ZnO films in the amorphous as a light scattering layer are also found with an infrared 980 nm laser as excitation source.